Application of adaptive virtual synchronous generator based on improved active power loop in photovoltaic storage systems - Youzhuo Zheng; Yutao Xu; Yekui Yang; Long Hua; Yuqing Yang (Frontiers in Energy Research)
In the process of integrating distributed energy, photovoltaic (PV) power generation systems encounter issues of intermittency and volatility, posing significant challenges to the stability of the power grid. Numerous studies have explored various control strategies to address these challenges, including droop control, virtual synchronous generator (VSG) control, and others. However, existing methods often struggle to provide sufficient inertia and damping support to the power system, particularly under dynamic conditions. This paper aims to address these limitations by introducing an adaptive inertia control method based on an improved active power loop in a PV-storage system. This method aims to optimize the impact and instability phenomena that occur during the integration of distributed PV, reduce system fluctuations, decrease the overshoot of oscillations, and enhance the dynamic performance of the system. Firstly, the mathematical models and control methods of photovoltaic cells and batteries are introduced. Secondly, the control principle of the traditional VSG is explained. Then, the adaptive inertia algorithm is incorporated into the active power loop of the VSG control, and an adaptive inertia control method based on the improved active power loop is proposed. Finally, the effectiveness of the proposed method is verified through simulations.